Romanticism, Origins, and the History of Heredity - Lehleiter, Christine (Bucknell University Press, 2014)
Examining novels, studies on plant hybridization, treatises on animal breeding, and collections of anatomical monstrosities, Origins Matter delineates how romantic authors imagined the ramifications of emerging notions of heredity for the conceptualization of selfhood.
Description based on publisher supplied metadata and other sources
Keywords: Deutsch; Literatur; Vererbung; Fortpflanzung